The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Treatment and Prevention of Malaria 2011
DOI: 10.1007/978-3-0346-0480-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers of Plasmodium Resistance to Antimalarials

Abstract: Investigations into the molecular basis of Plasmodium parasite resistance to antimalarial drugs have made strong progress in defining key determinants. Mutations in the digestive vacuole transmembrane proteins P. falciparum chloroquine resistance transporter (PfCRT) and P. falciparum multidrug resistance protein 1 (PfMDR1) are important drivers of parasite resistance to several quinolinebased drugs including chloroquine, amodiaquine, and to a lesser extent quinine. Amplification of pfmdr1 can also mediate resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 178 publications
0
16
0
Order By: Relevance
“…Multiple investigations have focused on pfmdr1 , which encodes an ATP-binding cassette (ABC) transporter resident on the digestive vacuole and can vary via point mutations or copy number [42]. Field studies and laboratory investigations demonstrate that pfmdr1 gene amplification is associated with an increased risk of parasite recrudescence following mefloquine or artesunate–mefloquine treatment, and in-vitro resistance to mefloquine accompanied by reduced susceptibility to ART [36,54,55].…”
Section: Recent Advances In Defining Artemisinin Mode Of Action and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple investigations have focused on pfmdr1 , which encodes an ATP-binding cassette (ABC) transporter resident on the digestive vacuole and can vary via point mutations or copy number [42]. Field studies and laboratory investigations demonstrate that pfmdr1 gene amplification is associated with an increased risk of parasite recrudescence following mefloquine or artesunate–mefloquine treatment, and in-vitro resistance to mefloquine accompanied by reduced susceptibility to ART [36,54,55].…”
Section: Recent Advances In Defining Artemisinin Mode Of Action and Mmentioning
confidence: 99%
“…Several parasite proteins have been implicated in decreased susceptibility to artemisinins (ARTs), including PfATP6 (proposed to be in the endoplasmic reticulum [41]), PfMDR1 on the digestive vacuole [42], PfMRP1 on the parasite plasma membrane [43], and UBP-1 whose ortholog in Plasmodium chabaudi is associated with ART resistance [44]. The digestive vacuole protein PfCRT is also indicated as mutations that confer chloroquine resistance have been shown to significantly increase susceptibility to ARTs [45].…”
Section: Figurementioning
confidence: 99%
“…Dihydrofolate reductase (DHFR) and dihydropteroate synthase (DHPS) are known targets of pyrimethamine and sulfadoxine, respectively [4]. These drugs specifically inhibit the enzymes of the folate pathway to kill the parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that treatment with artemether-lumefantrine selects for the pfmdr1 wild-type N86 allele [810]. Pfmdr1 amplification resulting in multiple gene copies is associated with resistance to amino alcohols (mefloquine and lumefantrine) [4, 11]. Recent studies have demonstrated that mutations in Kelch propeller 13 is directly associated with artemisinin resistance [12].…”
Section: Introductionmentioning
confidence: 99%
“…We also note that PND activity does not appear to be significantly influenced by variant alleles of pfcrt and pfmdr1, which are common to field isolates and which are known to be major determinants of parasite resistance to chloroquine and ADQ (62)(63)(64). These genes encode transporters present on the digestive vacuole membrane, where they appear to modulate drug accumulation in this acidic compartment and regulate drug access to heme (65,66).…”
Section: Figmentioning
confidence: 79%